2010
DOI: 10.1093/nar/gkq046
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Smad1 MH1/DNA complex reveals distinctive rearrangements of BMP and TGF-β effectors

Abstract: Smad1 is a downstream effector of the BMP signaling pathway that binds regulatory DNA to execute gene expression programs leading to, for example, the maintenance of pluripotency in mice. On the contrary, the TGF-β-activated Smad3 triggers strikingly different programs such as mesodermal differentiation in early development. Because Smad1 and Smad3 contain identical amino acids at the DNA contact interface it is unclear how they elicit distinctive bioactivities. Here, we report the crystal structure of the MH1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(100 citation statements)
references
References 60 publications
3
97
0
Order By: Relevance
“…Next, we extended the analysis and included a total of six TFs belonging to POU classes I, II, III, V, and VI (Figs 1E and F, and EV1B). We quantified the cooperativity of the homodimeric Oct–Oct and heterodimeric Sox–Oct binding of the POU proteins to the MORE ( OctOct ) and SoxOct elements using previously derived equations 27, 40. Cooperativity represents the ratio of the equilibrium binding constant for the binding of a factor to free DNA to the binding of DNA in the presence of another protein (Sox2 for heterodimers and another POU factor for homodimers).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we extended the analysis and included a total of six TFs belonging to POU classes I, II, III, V, and VI (Figs 1E and F, and EV1B). We quantified the cooperativity of the homodimeric Oct–Oct and heterodimeric Sox–Oct binding of the POU proteins to the MORE ( OctOct ) and SoxOct elements using previously derived equations 27, 40. Cooperativity represents the ratio of the equilibrium binding constant for the binding of a factor to free DNA to the binding of DNA in the presence of another protein (Sox2 for heterodimers and another POU factor for homodimers).…”
Section: Resultsmentioning
confidence: 99%
“…Cooperativity factors (ω) were calculated after quantifying the fraction of bound DNA in EMSAs using the below equations. Equations were derived using Boltzmann weights and principles of statistical mechanisms as detailed in 27, 40.…”
Section: Methodsmentioning
confidence: 99%
“…In all cases, an 11-residue b-hairpin was shown to be responsible for DNA sequence recognition, and is embedded in the major groove of DNA ( Fig. 1C -E) (Shi et al 1998;Baburajendran et al 2010Baburajendran et al , 2011. The amino acids responsible for specific contacts with the bases are conserved in all three MH1 domains ( Fig.…”
Section: Dna Binding Of Smad Complexes and Its Regulation By Posttranmentioning
confidence: 99%
“…The crystal structure of the SMAD1 MH1 domain revealed that the DNA contact interface of SMAD1 is rearranged compared with that of SMAD3, and, as a consequence, several key DNA backbone interactions are inhibited (Baburajendran et al 2010). In the SMAD1 MH1 domain, the amino-terminal a1 helix is dislodged from the intramolecular binding site seen in the SMAD3 MH1 domain (Fig.…”
Section: Dna Binding Of Smad Complexes and Its Regulation By Posttranmentioning
confidence: 99%
See 1 more Smart Citation